DIAGNOSIS OF SPONTANEOUS BACTERIAL PETITONITIS WITH ETIOLOGY OF LIVER CIRRHOSIS AND MODERN TREATMENT METHODS - Shukhrat T. Urokov; Jakhongir D. Komilov (Central Asian Journal of Medicine, 2025)
This article analyzes the data on the examination and treatment of 126 patients with spontaneous bacterial peritonitis of liver cirrhosis etiology treated in the surgical department of the Bukhara branch of the Bukhara State Medical Institute, the clinical base of the Department of "Surgical Diseases in Family Medicine" of the Bukhara State Medical Institute during 2016-2024. The purpose of the study: to conduct a comparative study of the diagnostics and modern treatment methods of spontaneous bacterial peritonitis of liver cirrhosis etiology.